Effects of Micro-Osteoperforation Depths on Canine Retraction Rate and Root Resorption: A Systematic Review and Meta-Analysis - Inpanya, Potjanakorn; Chanmanee, Pannapat; Teerakanok, Supontep (European Journal of Dentistry, 2025)
This systematic review and meta-analysis aimed to compare canine retraction rates and the amounts of root resorption in different depths of micro-osteoperforations (MOPs) during canine retraction in orthodontic patients. Relevant literature was sought using a prespecified search strategy until May 2024. Electronic medical and scientific databases included PubMed/MEDLINE, Scopus, EMBASE, Web of Science, and the Cochrane's Library (clinical trials). The review protocol was registered in Prospero (CRD42024555722). The data were analyzed in terms of mean difference for comparison using a random-effect meta-analysis. A total of 14 randomized controlled trial studies were included. According to the findings of the meta-analysis on MOPs and their impact on the mean rate of canine movement, the MOP groups showed a significantly higher rate compared with the control groups (weighted mean difference = 0.32; 95% confidence interval [CI], 0.24–0.40; p = 0.00 and weighted mean difference = 0.20; 95% CI, 0.01–0.40; p = 0.04) at depths of 2 to 4 and 5 to 7 mm, respectively. Three studies reported no differences in root resorption between the MOP groups and the control groups. Both MOP depths, that is, 2 to 4 and 5 to 7 mm, accelerated canine retraction more than the controls by approximately 0.32 and 0.20 mm/month, respectively. However, both MOP depths presented root resorption during canine retraction that was not different from the controls.
Keywords: orthodontics; micro-osteoperforation; tooth movement; meta-analysis; systematic review